Reconhecimento da ligação dos anticorpos anti-HCV com proteínas recombinantes do vírus da hepatite C por meio do teste ELISA - Souza, Laís Cristina de (Universidade Federal de São Carlos, 2016)
Viral hepatitis is a major public health problem worldwide and in Brazil. They are notifiable diseases and according to estimates, billions of people have had contact with the hepatitis and millions are chronic carriers. Infection with hepatitis C virus (VHC) is a major problem worldwide public health due to the high rate of progression to chronicity, the evolutionary potential for cirrhosis and hepatocellular carcinoma, major complications leading to death. In general it can be said that in the last decade there have been major advances in the diagnosis of hepatitis C. In this period there was progressive improvement in sensitivity and specificity of the tests used to detect antibodies against the VHC virus. However, it is necessary that more accurate tests are developed. Thus, considering that the concern for the detection of hepatitis C increases every day, especially in blood banks; the diagnostic methods of this infection are of great clinical relevance and may be used as markers chronicity and indicative of therapeutic efficacy. Therefore, this work proposed to evaluate the connection and recognition of anti-VHC antibody positive and positive genotyped samples in patients with hepatitis C through the standardization of procedures and solutions used in qualitative ELISA. There was the process of awareness of microplates with recombinant chimeric protein, made the analysis of sensitivity, specificity, reproducibility and validity of the method. We obtained from ELISA assays with standardized recombinant proteins a protocol able to have a good performance of the main components of the reaction, and antigens conjugated with good resolution. This study presented ELISA results valid 95.69%, 100% reproducibility, 94.5% sensitivity and specificity 99.3%, higher than the ELISA performed with multiepitopo protein MEHCV who presented with sensitivity (92.86%) and specificity (82.89%). The standard ELISA can be used as a qualitative serological technique aimed at detection of anti-VHC antibodies, as demonstrated with great reactivity in patients infected with VHC.
Keywords: Hepatitis C; VHC; ELISA and recombinant proteins; Proteínas recombinantes; ELISA; OUTROS